2016
DOI: 10.5897/jpbcs2016.0614
|View full text |Cite
|
Sign up to set email alerts
|

A method of estimating broad-sense heritability for quantitative traits in the type 2 modified augmented design

Abstract: Heritability is a basic genetic parameter for quantitative traits that may determine their selection generation and intensity as well as predict their selection response and efficiency in plant breeding. Estimation of heritability varies based on experimental design. The type 2 modified augmented design (MAD2) as an unbalanced experimental design, has been proposed for evaluating numerous unreplicated test genotypes with several replicated control genotypes to adjust for soil heterogeneity. Here, we define an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…High values of h 2 BS indicate that most of the phenotypic variations observed for these traits are genetic in nature and the possibility of genetic gains is increased. You et al (2016) found high heritability (h 2 BS) ([ 0.90) for linoleic and linolenic acid, whereas a moderate heritability for fat content (0.50-0.70). These results are consistent with those of Pleines and Friedt (1988), Khan et al (2008), andSpasibionek (2013), who observed high h 2 BS when controlling these same traits in Brassica.…”
Section: Genetic Parameter Estimationmentioning
confidence: 95%
“…High values of h 2 BS indicate that most of the phenotypic variations observed for these traits are genetic in nature and the possibility of genetic gains is increased. You et al (2016) found high heritability (h 2 BS) ([ 0.90) for linoleic and linolenic acid, whereas a moderate heritability for fat content (0.50-0.70). These results are consistent with those of Pleines and Friedt (1988), Khan et al (2008), andSpasibionek (2013), who observed high h 2 BS when controlling these same traits in Brassica.…”
Section: Genetic Parameter Estimationmentioning
confidence: 95%
“…The limited number of seeds per genotype and the large number of genotypes are the reasons for using this augmented design (Mramba et al, 2018). Compared to the randomized complete block design, which requires replication of the genotypes tested in each block, in an extended randomized group design or augmented design, replication was only made to the check genotypes (commercial varieties) (Frank et al, 2016). Variability can be controlled, and genotypes efficiently can be assessed through augmented design.…”
Section: Experimental Designmentioning
confidence: 99%
“…This design gives indicative estimations about the inheritance of traits studied. Frank et al (2026) and Chandana et al (2018) calculated genetic components based on variance calculations obtained from augmented design (Frank et al, 2016;Chandana et al 2018).…”
Section: Introductionmentioning
confidence: 99%